XIIIThe Victorian Period. Issue 1 (13th August 2022) - Garza, Ana Alicia; Burke, Lois; Snailham, Fiona; Blackburn-Daniels, Sally; Hind, Heather; Baker, William
Abstract: This chapter has six sections: 1. General and Prose, including Dickens; 2. The Novel; 3. Poetry; 4. Periodicals, Publishing History; 5. Miscellaneous; 6. Drama. Section 1 is by Ana Alicia Garza; section 2 is by Lois Burke and Fiona Snailham; section 3 is by Sally Blackburn-Daniels; section 4 is by Heather Hind; sections 5 and 6 are by William Baker.